Flavonoid, hesperidine, total phenolic contents and antioxidant activities from Citrus species - Abd Ghafar, Mohammed Fadlinizal; Prasad, K. Nagendra; Kong, Kin Weng; Ismail, Amin (Academic Journals, 2010)
Citrus has long been regarded as a food and also as a medicinal plant. Fruits of four species of citrus which are commonly available in Malaysia, namely C. hystrix(wild lime), C. aurantifolia (common lime), C. microcarpa (musk lime) and C. sinensis (orange), were chosen to investigate their total phenolic, flavonoid and hesperidine contents. Additionally, the antioxidant activities were also determined by ferric reducing antioxidant power (FRAP) and 1,1-diphenyl-2-picryl hydrazyl (DPPH) radical scavenging activity. C. hystrix had the highest flavonoid and total phenolic contents while C. aurantifolia had the highest hesperidine content. The antioxidant activity of C. hystrix was highest determined by FRAP and DPPH assays compared to other citrus species. A strong positive correlation of R2 = 0.9090 between total phenolic content and FRAP values was observed in this investigation.This study indicated that C. hystrix exhibited the highest antioxidant, flavonoid and phenolic content and can be used potentially as a readily accessible source of natural antioxidant.